2018
DOI: 10.1101/373134
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Automated 3-D mapping of single neurons in the standard brain atlas using single brain slices

Abstract: 11Recent breakthroughs in neuroanatomical tracing methods have helped unravel 12 complicated neural connectivity in whole brain tissue at a single cellular resolution. 13However, analysis of brain images remains dependent on highly subjective manual 14 processing. In the present study, we introduce AMaSiNe, a novel software for 15 automated mapping of single neurons in the standard mouse brain atlas. The AMaSiNe 16 automatically calibrates alignment angles of each brain slice to match the Allen 17Reference Atl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Moreover, though registration-based methods can achieve full anatomical annotation in reference to a standard atlas for whole-brain datasets, their region-based 3D registration to a whole-brain atlas lacks the flexibility to analyze incomplete brain datasets or those focused on a certain volume of interest ( Song and Song, 2018 ), which is often the case in neuroscience research. Though some frameworks can register certain types of brain slabs that contain complete coronal outlines slice by slice ( Fürth et al, 2018 ; Song and Song, 2018 ; Ferrante and Paragios, 2017 ), it remains very difficult to register a small brain block without obvious anatomical outlines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, though registration-based methods can achieve full anatomical annotation in reference to a standard atlas for whole-brain datasets, their region-based 3D registration to a whole-brain atlas lacks the flexibility to analyze incomplete brain datasets or those focused on a certain volume of interest ( Song and Song, 2018 ), which is often the case in neuroscience research. Though some frameworks can register certain types of brain slabs that contain complete coronal outlines slice by slice ( Fürth et al, 2018 ; Song and Song, 2018 ; Ferrante and Paragios, 2017 ), it remains very difficult to register a small brain block without obvious anatomical outlines.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, though registration-based methods can achieve full anatomical annotation in reference to a standard atlas for whole-brain datasets, their region-based 3D registration to a whole-brain atlas lacks the flexibility to analyze incomplete brain datasets or those focused on a certain volume of interest ( Song and Song, 2018 ), which is often the case in neuroscience research. Though some frameworks can register certain types of brain slabs that contain complete coronal outlines slice by slice ( Fürth et al, 2018 ; Song and Song, 2018 ; Ferrante and Paragios, 2017 ), it remains very difficult to register a small brain block without obvious anatomical outlines. As neural networks have emerged as a technique of choice for image processing ( Long et al, 2015 ; Chen et al, 2018a ; He et al, 2019 ; Zhang et al, 2019 ), deep-learning-based brain mapping methods have also recently been reported to directly provide segmentation/annotation of primary regions for 3D brain datasets ( Iqbal et al, 2019 ; Akkus et al, 2017 ; Chen et al, 2018b ; Milletari et al, 2017 ; de Brebisson and Montana, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…First, creating the transforms by manual input can be timeconsuming when an experiment involves many brain slices. In a future version, SHARP-Track's manual features could be combined with an algorithm to automatically register slices such as that found in Song et al, 2018. Second, we found that there remains some error and inconsistency in marking electrode trajectories (Figure 4).…”
Section: Discussionmentioning
confidence: 88%
“…We recommend prioritizing that the transform is accurate nearby the region of interest. An alternative approach could incorporate non-rigid transformations as in Fürth et al, 2018, Song et al, 2018, and Xiong et al, 2018 One feature generally lacking in electrodelocalization toolkits is the use of brain regions' distinct electrophysiological signatures. A future Figure 4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation